2009
DOI: 10.1097/qad.0b013e32831cc114
|View full text |Cite
|
Sign up to set email alerts
|

Inferiority of IL-2 alone versus IL-2 with HAART in maintaining CD4 T cell counts during HAART interruption: a randomized controlled trial

Abstract: Objective To evaluate if interleukin (IL)-2 in patients with chronic HIV infection can maintain CD4 T cell counts during 6 months of highly active antiretroviral therapy (HAART) interruption. Design Prospective, randomized, controlled, open-label phase II non-inferiority trial comparing IL-2 with HAART interruption or continuous HAART (ICARUS). Methods 41 IL-2-experienced (≥3 prior cycles) HIV-1-infected adults with CD4 ≥500 cells/µl were randomized 2:1 to Interrupted (I=27) or Continuous (C=14) HAART for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The second study [21, 22] consisted of 40 chronically HIV-infected IL-2-experienced adults who were on HAART therapy prior to receiving a baseline cycle of IL-2 (subcutaneous injections of 7.5 million international units twice daily). Subjects were then randomized 2:1 either to interrupt or continue HAART for 6 months, during which time additional IL-2 cycles were administered with 10 days of peri-cycle HAART, if CD4 T cell counts fell below 90% of baseline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second study [21, 22] consisted of 40 chronically HIV-infected IL-2-experienced adults who were on HAART therapy prior to receiving a baseline cycle of IL-2 (subcutaneous injections of 7.5 million international units twice daily). Subjects were then randomized 2:1 either to interrupt or continue HAART for 6 months, during which time additional IL-2 cycles were administered with 10 days of peri-cycle HAART, if CD4 T cell counts fell below 90% of baseline.…”
Section: Methodsmentioning
confidence: 99%
“…The first study [19, 20] evaluated the effect of 3–6 IL-2 cycles added to single or dual nucleoside analogue therapy administered over 1 year compared to antiretroviral therapy alone. The second study [21, 22] evaluated the effect of a baseline IL-2 cycle in patients who either subsequently interrupted or continued HAART for 6 months. Biomarkers and immune parameters were analyzed pre- and post-IL-2 administration, as well as long-term at the end of each trial, in order to characterize the duration of any IL-2 effect, its relationship to HIV viremia and changes in CD4 T cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…IL-2 is already used in the clinic to expand and maintain CD4 + T cell numbers in patients with HIV infection137,138 and as an anti-cancer agent, and this is showing efficacy in treating some patients with melanoma and renal cell carcinoma139. The related cytokine IL-15, the receptor of which consists of IL-2Rβ, γ c and IL-15Rα (FIG.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…The authors concluded that although treatment interruption is not recommended, the use of IL-2 could lengthen the time before ART would need to be restarted. However, contrary to this data, the ICARUS study showed treatment interruption with IL-2 was inferior to IL-2 treatment with continuous HAART in maintaining CD4 + counts[127]. More recently, two additional studies were conducted to evaluate IL-2 treatment with treatment interruption.…”
Section: Potential Therapeutic Roles Of Cytokines In Hivmentioning
confidence: 99%